2020
DOI: 10.1021/jacs.0c00542
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Metal–Organic Frameworks Directly Monitored through In Situ Variable Temperature Liquid-Cell Transmission Electron Microscopy and In Situ X-ray Diffraction

Abstract: Zr6-based metal–organic frameworks (MOFs) with tetratopic organic linkers have been extensively investigated owing to their versatile structural tunability. While diverse topologies and polymorphism in the resulting MOFs are often encountered with tetratopic linkers and Zr6 nodes, reports on phase transitions within these systems are rare. Thus, we have a limited understanding of polymorph transformations, hindering the rational development of pure phase materials. In this study, a phase transition from a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 50 publications
1
92
0
Order By: Relevance
“…reported that scu ‐NU‐906 and csq ‐NU‐1008 could be built from the Zr 6 nodes and H 4 TCPB‐Br 2 linker when benzoic acid and formic acid were used as modulators in DMF, respectively. [ 75 ] Then, Chen et al. reported the preparation of scu ‐NU‐906 and csq ‐NU‐1008 by using different modulators or solvents.…”
Section: Phase Engineering Of Mofsmentioning
confidence: 99%
“…reported that scu ‐NU‐906 and csq ‐NU‐1008 could be built from the Zr 6 nodes and H 4 TCPB‐Br 2 linker when benzoic acid and formic acid were used as modulators in DMF, respectively. [ 75 ] Then, Chen et al. reported the preparation of scu ‐NU‐906 and csq ‐NU‐1008 by using different modulators or solvents.…”
Section: Phase Engineering Of Mofsmentioning
confidence: 99%
“…This was especially aimed to the study of metal organic frameworks (MOFs), one of the most emerging topics with fundamental need to understand structure-properties relationship. Hence, breakthrough developments in characterization techniques as cryogenic-TEM (cryo-TEM) [69] and High-Resolution TEM (HR-TEM) [70] paved the way to structural features at the nanometric scale as well as recent improvements for in situ measurements inter alia hot stage TEM, liquid cell TEM (LCTEM) [71] or environmental TEM (ETEM) [72] enabled to observe the dynamics of these systems. Advanced 3-dimensional electronic techniques as automated electron diffraction tomography (ADT) [73] and Rotation Electron Diffraction (RED) [74] were able to gather sufficient data for ab initio structure elucidation and thus succeeded where conventional diffraction techniques failed [75].…”
Section: Strategies To Identify and Achieve Polymorphs And The Influence On Their Properties 41 Identification Of Polymorphsmentioning
confidence: 99%
“…In this respect, different techniques have been developed to chemically image solid materials with nanoscale resolution and may be of great use in such cases. 420 An overview of the different methods available for chemical imaging can be found in the review authored by Buurmans and Weckhuysen, 56,421 but due to their suitability, we would like to highlight AFM coupled with Tip-Enhanced Raman Spectroscopy (TERS) and element specific X-ray nanotomography. These techniques have been successfully applied to different heterogeneous catalysts in order to obtain chemical maps with 20 nm and sub-30 nm resolution, respectively.…”
Section: Chemical Imaging and Spatially Resolved Studies Of Bulk Mofsmentioning
confidence: 99%
“…We refer the reader to recent literature on this type of techniques to understand the potential of microscopy for understanding crystallization of MOFs. 420,[463][464][465]…”
Section: Use Of Metal@mof Composites As Spectroscopic Toolsmentioning
confidence: 99%